Mass media in a changing world - Rodman, George R. (McGraw-Hill, 2011)
This engaging text introduces students to the world of media through a unique structure that makes the material easily intelligible and meaningful to their lives. Each chapter is divided into three-part narrative sections: history, industry, and controversy. Mass Media in a Changing World is the story of where the media came from, why they do what they do, and why those actions cause controversies. The Third Edition features updated statistics and current examples including the selling of the war in Iraq, shock jock Michael Savage, the work being done to save Darfur and much more!